(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The study examined the efficacy of counselling support techniques adopted in reducing drug abuse among adolescent students. In this study, survey research design was adopted. The population of the study was 312 guidance counsellors in public secondary schools in Anambra State. Simple random sampling technique was used to select 100 guidance counsellors for the study. A-24 item questionnaire validated by experts in the field of education was used for data collection. The reliability of the instrument was established using Cronbach’s alpha method, which yielded alpha values of 76 and .88 for counselling support techniques and efficacy respectively. Mean, standard deviation and t-test were used to analysis data collected. Some of the findings revealed that guidance counsellors to a high extent adopt enforcement of corporal punishment, having students sign undertaking on behavioural change, and zero-tolerance policies resulting in suspension or expulsion as support techniques for reducing drug abuse among adolescent students. The findings also revealed that majority of the counselling support techniques listed have high efficacy in reducing drug abuse among adolescent students. Furthermore, it was found that years of experience was a significant factor on guidance counsellors’ adoption of counselling support techniques in this regard. It was recommended among others that; Anambra State government should organize regular capacity training programmes for guidance counsellors in public secondary schools to enable them learn current drug intervention techniques.